2015
DOI: 10.1007/s10334-015-0500-9
|View full text |Cite
|
Sign up to set email alerts
|

Parameterization of hyperpolarized 13C-bicarbonate-dissolution dynamic nuclear polarization

Abstract: An optimized bicarbonate preparation and experimental procedure provided improved T1 and SNR values, allowing in vitro and in vivo applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Hyperpolarized bicarbonate ( 2 ) was the first and so far only ratiometric sensor applied both in vitro and in vivo . A main drawback of the molecule is its short T 1 ( in vivo ∼10 s at both 3 T and 9.4 T,) and a small SNR of 13 CO 2 at physiological pH due to the low p K a , …”
Section: Hyperpolarized Ph Sensor Moleculesmentioning
confidence: 99%
“…Hyperpolarized bicarbonate ( 2 ) was the first and so far only ratiometric sensor applied both in vitro and in vivo . A main drawback of the molecule is its short T 1 ( in vivo ∼10 s at both 3 T and 9.4 T,) and a small SNR of 13 CO 2 at physiological pH due to the low p K a , …”
Section: Hyperpolarized Ph Sensor Moleculesmentioning
confidence: 99%
“…Nevertheless, these concerns can likely be managed without serious detriment to the gains in SNR attainable with a multi‐excitation approach. One final consideration regarding clinical implementation of pH imaging is that the short BiC–CO 2 T 1 in vivo, measured as ~10 s within various mouse and/or rat tissues at field strengths ranging from 3–14T, may be prohibitive for future translation into patients. It has been suggested that this may be because of fast macromolecular binding–unbinding kinetics, in which case a short interstitial T 1 would be an insurmountable problem.…”
Section: Discussionmentioning
confidence: 99%
“…One final consideration regarding clinical implementation of pH imaging is that the short BiC–CO 2 T 1 in vivo, measured as ~10 s within various mouse and/or rat tissues at field strengths ranging from 3–14T, may be prohibitive for future translation into patients. It has been suggested that this may be because of fast macromolecular binding–unbinding kinetics, in which case a short interstitial T 1 would be an insurmountable problem. However, in humans there may be greater preservation of vascular HP BiC–CO 2 signal before tissue delivery, owing to a slower cardio‐respiratory cycle compared with rodents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations